Characterization and study of functional properties of banana starch green variety of Mysore (Musa AAB-Mysore) - Sabrina de Medeiros FONTES (Ciência e Tecnologia de Alimentos, 2017)
So that there is innovation in the development of food products with starch in its formulation, it can take into account the banana starch, which has higher content when the fruit is fully green. The starches and derivatives are used as ingredients or additives basic components added in small amounts to enhance the production, presentation and preservation of the product. This study aimed to characterize the green banana variety Mysore ( Musa AAB - Mysore), studying their functional properties as well as its importance and use in the food industry. The starch extracted from green bananas were performed physico-chemical studies and functional properties. The yield amounted to a starch quality, with characteristics similar to other species of bananas. The results of studies of its functional properties reveal a less prone to starch retrogradation phenomenon. Starch showed results that indicate its use in many areas of the food industry (chilled foods, soups, pates), especially for the preparation of sauces sector, becoming an alternative technology and development of food products.